Respostas

2013-09-03T19:27:53-03:00
Função de 1 grau:
f(x)= ax + b
então:
f(1)= a+b =5 (1)
f(-2) = -2a + b =1  (2)

fazendo (2) - (1) temos :
-2a+b -a-b = 1 -5
-3a = -4
a = 3/4 , substituindo em (1):
3/4 + b = 1
b = 4/4 - 3/4
b = 1/4, portanto
f(x) = (3/4)* x + 1/4
Na verdade, a = 4/3
só trocar assim?
Função de 1 grau:
f(x)= ax + b
então:
f(1)= a+b =5 (1)
f(-2) = -2a + b =1 (2)

fazendo (2) - (1) temos :
-2a+b -a-b = 1 -5
-3a = -4
a = 4/3 , substituindo em (1):
3/4 + b = 1
b = 4/4 - 3/4
b = 1/4, portanto
f(x) = (3/4)* x + 1/4
Vai ficar assim:
4/3 + b = 5
b = 15/3 - 4/3
b = 11/3, portanto
f(x) = (4/3)* x + 11/3